Yixin-Fumai granules improve sick sinus syndrome in aging mice through Nrf-2/HO-1 pathway: A new target for sick sinus syndrome. (15th September 2021) - Zhang, Heng; Li, Lingkang; Hao, Miao; Chen, Keyan; Lu, Yongping; Qi, Jing; Chen, Wei; Ren, Lu; Cai, Xintong; Chen, Chen; Liu, Zhuang; Zhao, Bin; et al.
Abstract: Ethnopharmacological relevance: Yixin-Fumai granules (YXFMs)—composed of Ginseng quinquefolium (L.) Alph. Wood, Ophiopogon japonicus (Thunb.) Ker Gawl, Schisandra arisanensis Hayata, Astragalus aaronsohnianus Eig, Salvia cryptantha Montbret & Aucher ex Benth, and Ligusticum striatum DC—are compound granules used in traditional Chinese medicine to increase heart rate and thus treat bradyarrhythmia. It may be effective in treating sick sinus syndrome (SSS). Aim: To observe the effect of YXFMs on aging-induced SSS in mice and explore whether this effect is related to the Nrf-2/HO-1 signaling pathway. Materials and methods: Mice with a significant decrease in the heart rate due to natural aging were selected to construct an SSS model. After the mice were administered YXFMs, the damage to their sinoartrial node (SAN) was assessed through electrocardiography, Masson's trichrome staining, and terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL). Dihydroethidium staining and immunofluorescence staining were used to assay reactive oxygen species (ROS) content and HCN4, respectively. Moreover, to observe the effects of YXFMs in vitro, the HL-1 cell line, derived from mouse atrial myocytes, was used to simulate SAN pacemaker cells, with H2 O2 used as the cellular oxidative stress (OS) inducer. 2, 7-Dichlorodihydrofluorescein diacetate staining was used to assay ROS content, whereas immunofluorescence staining and Western blotting were used to elucidate the related protein expression. Finally, mice were injected the Nrf-2 inhibitor ML385 to reversely verify the effects of YXFMs. Results: In our in vivo experiments, YXFMs significantly inhibited aging-induced SSS, shortened the R-R interval, increased heart rate, alleviated fibrosis, reduced apoptosis rate and ROS content, and promote HCN4 expression in the SAN. In our in vitro experiments, YXFMs significantly inhibited H2 O2 -induced cell peroxidation damage, promoted Nrf-2 activation and nuclear metastasis, increased HO-1 expression— thereby inhibiting ROS accumulation—and finally, upregulated HCN4 expression through the inhibition of histone deacetylase 4 (HDAC4) expression and its nuclear metastasis. Finally, injection of the Nrf-2 inhibitor ML385 after YXFMs administration inhibited their protective effect in the mice. Conclusion: Here, we elaborated on the relationship between aging-induced SSS and the Nrf-2/HO-1 pathway for the first time and proposed that YXFMs improve SSS via the Nrf-2/HO-1 axis. Specifically, YXFMs promoted Nrf-2 activation and plasma–nuclear transfer to enhance HO-1 expression via the Nrf-2/HO-1 axis. This inhibited OS and reduced ROS accumulation in the SAN, and then, through the ROS/HDAC4 axis, reduced HDAC4 expression and plasma–nuclear transfer. Thereby, the OS-induced HCN4 loss in the SAN was inhibited—improving the function of I f channel and thus producing SAN protection effect against SSS and improving the heart rate and R-R interval. In the future, we plan to use bioinformatics analysis technology to execute the next step of our research, namely to determine the effect of isolated, purified components of YXFMs in SSS, to increase its efficiency and reduce the toxicity of YXFMs. Graphical abstract: This study elaborates the relationship between SSS and the Nrf-2/HO-1 pathway and proposes for the first time that Nrf-2/HO-1 is possibly an important target for SSS alleviation. This study also verifies the therapeutic effect of YXFMs on SSS, demonstrating that the underlying mechanism is related to the Nrf-2/HO-1 pathway; thus, YXFMs have potential clinical applications. Image 1